Effect of Addition of Moringa (Moringa oliefera) in The Feed on Conception Rate, Litter size and Survival Rate of Local Rabbits in Indonesia - Habib Hilal Hamdi; Ragil Angga Prastiya; Trilas Sardjito; Ikmalia 'Amaliy; Sofiya Wulandari; Imana Fitri Adila; Tri Ena Wulandari; Nining Haryuni; Nagia Musa Alghoul (The Indian Veterinary Journal, 2024)
Moringa leaves contain galactagogues that can enhance milk production in local rabbits trough the stimulation of oxytocin and prolactin hormones. This study aimed to assess the effects of moringa leaves on pregnancy, litter size, and survival rate of local rabbits. Twenty female rabbits and three male rabbits were used as experimental animals. The study comprised two treatments: R0 (control) and R1 (feed supplemented with moringa leaves). Treatments were administered during pregnancy until the offspring reached 30 days of age. Data analysis was performed using a simple t-test. Study indicated that had a non-significant effect on pregnancy rates, with a percentage of 90% for rabbits fed moringa leaf flour and 80% for those without it. Furthermore, the provision of moringa leaf flour did not significantly affect litter size, with 46 offspring born to rabbits given moringa leaf flour and 41 born to those not given it. However, the provision of moringa leaf flour significantly improved the survival rate, with 100% survival among rabbits given moringa leaves compared to 75% among those not given them.